Trust and mixed signals: A study of religion, tattoos and cognitive dissonance. (July 2016) - Timming, Andrew R.; Perrett, David
Abstract: This paper examines trust judgements in the context of 'mixed signals', whereby the medium through which a signal is projected suggests untrustworthiness, but the signal itself suggests trustworthiness. Under conditions of 'mixed signals', trusters are left in a potential state of cognitive dissonance. The results of the research suggest that the presence of a tattoo lowers evaluations of trust across the board, but that Christian respondents rated faces with a Christian-themed tattoo significantly higher than non-Christian respondents. Nevertheless, among Christian respondents, there was no significant difference on trustworthiness ratings between a Christian-themed tattoo and non-Christian-themed tattoo. The results of the research have implications in relation to the psychological study of trust, religion and body art. Highlights: The paper examines trust judgements in the context of 'mixed signals'. The presence of a visible tattoo lowers trust judgements across the board. Christian respondents rated Christian-themed tattoos higher than non-Christians. Among Christians, Christian tattoos and non-Christian tattoos are rated equally.